EFFECT OF DEMONSTRATION IN TRANSFERRING FISH PROCESSING TECHNOLOGY - THIAGARAJAN, R; KANDORAN, M K (Fishery Technology, 2017)
A group of 28 fisherwomen who attended demonstration on three subjects, namely, preparation of fish wafers, fish pickles and fish soup powder showed significant knowledge and skill gain for all the three messages. The total knowledge and skill gain was maximum for preparation of fish wafers followed by that for preparation of fish soup powder and fish pickles.